More Than Words: Connecting Diverse Communities Through Public Signage Translation in Demak Regency (Universitas Terbuka, 2025)
In heritage destinations like Demak Regency, public signage is a critical interface for connecting with diverse, international communities. Proper translation can transform these signs into linguistic bridges, fostering inclusivity and a welcoming atmosphere. This study investigates how current translation practices on public signage in Demak support or undermines this goal. The research employs a qualitative case study methodology, analyzing 50 bilingual signs through a dual framework: assessing accuracy using the model by Nababan et al. (2012) and evaluating the effectiveness of intercultural community bridging using a framework adapted from Byram (1997). The findings reveal that an over-reliance on the literal translation technique is systemic. This results in an average accuracy score of 2.22 (Less Accurate) and, more critically, an average community bridging score of 2.0 (Moderate). This demonstrates that even when translations are partially understandable, they frequently fail as acts of intercultural hospitality, creating linguistic and cultural barriers. This paper argues that a conscious shift from literalism towards functional, target-oriented techniques like established equivalence is essential. By doing so, Demak can transform its public signage from simple directives into powerful tools that are